Age, Growth, and Sexual Maturity of the Crocodile Shark, Pseudocarcharias kamoharai, From the Eastern Atlantic Ocean - Kindong, Richard; Wang, Haozhan; Wu, Feng; Dai, Xiaojie; Tian, Siquan (Frontiers in Marine Science, 2020)
To better manage fish stocks, fisheries scientists use various data, including age and growth, to inform stock assessments and provide management advice. However, many non-targeted species, important to the marine ecosystem, including Pseudocarcharias kamoharai still lack such studies which may impede comprehensive assessment of stock status. This study presents the age, growth, and sexual maturity of this species from the Tropical Eastern Atlantic Ocean by examining vertebral samples and reproductive tracts. All samples were collected by Chinese Tuna Fishery Scientific Observers between November 2012 and May 2020, with sizes ranging from 46 to 101 cm fork length (FL). Four age enhancement techniques applied on whole and sectioned vertebral centra were compared. Four growth models fitted to the age data were also compared and the corrected Akaike information criterion was used to select the most plausible model. Whole vertebral centra stained with alizarin red S solution showed clearer growth band-pairs, and age ranged from 2 to 10 years (females) and from 2 to 11 years (males). No significant differences were observed in growth and age composition by sex in the sample. The three-parameter von Bertalanffy growth function presented the best fit to describe the growth of combined sexes of this species (L∞ = 107.8 cm FL, k = 0.18 year–1). Male specimens attained age-at-50% maturity (4.55 years) earlier than females (5.91 years). The estimated longevities were 11.95 and 13.33 years for females and males, respectively. The present study provides useful life history information, intending to elucidate the biology of this poorly managed shark species.